2004
DOI: 10.1360/04wc0142
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of root architecture in an applied core collection for phosphorus efficiency of soybean germplasm

Abstract: In the present study, we constructed an "applied core collection" for phosphorus (P) efficiency of soybean germplasm using a GIS-assisted approach. Systematic characterization and comparative analysis of root architecture were conducted to evaluate the relationship between root architecture and P efficiency and its possible evolutionary pattern. Our results found that: i) root architecture was closely related to P efficiency in soybean. Shallow root architecture had better spatial configuration in the P-rich c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 1 publication
(1 reference statement)
0
81
0
1
Order By: Relevance
“…In addition to the intrinsic involvement of GmEXPB2 in root system architecture changes in response to abiotic stress, it is reasonable to speculate that GmEXPB2 may have great potential in improving plant P efficiency. GmEXPB2 was cloned from HN89, a P‐efficient genotype, which was previously shown to acquire more P through improved root system architecture (Zhao et al. , 2004; Yan et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the intrinsic involvement of GmEXPB2 in root system architecture changes in response to abiotic stress, it is reasonable to speculate that GmEXPB2 may have great potential in improving plant P efficiency. GmEXPB2 was cloned from HN89, a P‐efficient genotype, which was previously shown to acquire more P through improved root system architecture (Zhao et al. , 2004; Yan et al.…”
Section: Discussionmentioning
confidence: 99%
“…, 2010). It has been reported that P‐efficient soybean genotypes respond to Pi starvation via alterations in the root system architecture and morphology associated with enhanced exploration for soil P (Zhao et al. , 2004; Yan et al.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in situ and dynamic observation and modeling are very important for assessing the rice root architecture. It cannot be simply classified by qualitative measurements made at a single point in time (Zhao et al. , 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to recognize that genotypic differences exist in terms of Pi acquisition from the soil. Studies have shown that for bean, soybean, and maize, P‐efficient plant lines employ shallower root growth angles that allow them to acquire more Pi from the P‐rich topsoil, thereby allowing better growth under P‐limiting conditions compared to less efficient genotypes (Zhao et al ; CalderĂłn‐VĂĄzquez et al ; Lynch ). In barley, genotypes having the ability to develop longer root hairs, and thereby achieve enhanced root penetration and root‐soil contact, through increased surface area, similarly exhibit higher yield potential in P‐limited soils (Gahoonia and Nielsen ; Haling et al ).…”
Section: Physiological and Biochemical Reprogramming In Response To Pmentioning
confidence: 99%